ASPEK REPRODUKSI IKAN SELAIS KAPOREH (Ompok eugeneiatus) DI SUNGAI KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Marhasak Stephen H; Roza Elvyra; Yusfiati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Floodplain river ecosystem in Kampar River of Riau Province has a unique water characteristics. This area was the production center of freshwater fish in Riau. Selais fish was the maskot of Pekanbaru city and typical food from Riau. Selais Kaporeh(Ompok eugeneiatus) is one of fish in Buluh Cina and Mentulik and known to have high economic value in Kampar district. The objectives of this research were to determine the reproduction aspect of Selais Kaporeh including the level of gonads maturity(TKG), index of gonads maturity, fecundity and reproductive potential. This study had been conducted from February to April 2013 in Buluh Cina and Mentulik village. The samples were collected using survey method. The numbers of Selais Kaporeh collected were 155 fishes that consist of 137 females and 18 males, with sex ratio 7,61:1. The length of female fish ranged between 9,3-20,3 cm and weight ranged from 3,1-34,7 g.The length of males range were between 10-14,9 cm and weight range were 2.5-10.8 g. The gonads maturity level of female and male of Selais Kaporeh fish observed rangedfrom TKG I-IV. The index of gonads maturity (IKG) from female and male fish from TKG I-IV were between 0-10,82% and 0-4,4%. IKG increased following TKG and decreased after spawnings. Fecundity were 1825 eggs. Selais Kaporeh did not lay eggs simultaneously in one spawning season and they tend to spawn throughout the year.